INNOVATIVE APPROACHES IN FOREIGN LANGUAGE TEACHING THROUGH DIGITAL TECHNOLOGIES: INNOVATIVE APPROACHES IN FOREIGN LANGUAGE TEACHING THROUGH DIGITAL TECHNOLOGIES - Bekbaulieva, Rano (Журнал иностранных языков и лингвистики, 2025)
During this age of technology and digital advancements the realm of teaching languages has seen a notable evolution. Old school teaching techniques centered around memorization, grammar exercises and textbook focused lessons are now making room for resources that promote interaction, ease of access and personalized learning experiences. As stated by Godwin Jones (2018) online platforms empower learners to customize their learning journeys and receive feedback resulting in motivation and academic achievement.